Comparison between inhalational anesthetics in terms of DNA damage and immunological markers - Braz, Mariana G. [UNESP] (2024)
This study compared genetic damage and immunological markers between surgical patients who underwent inhalational anesthesia with isoflurane or sevoflurane. Blood samples were collected from surgical patients (n = 18 in the isoflurane group and n = 17 in the sevoflurane group) at baseline (before the anesthesia procedure) and the day after anesthesia. DNA damage was detected using an alkaline comet assay; proinflammatory interleukin (IL)-6 was detected by flow cytometry, and white blood cells were detected via an automatic hematology analyzer. The characteristics of both groups were similar, and neither of the two anesthetics induced DNA damage. Similarly, mild neutrophilia was observed after anesthesia in both groups. Increased IL-6 levels were observed 1 day after anesthesia regardless of the type of anesthetic, but this increase was greater in the isoflurane group. Our study suggested that isoflurane and sevoflurane administration may contribute to changes in the immune parameters measured, though no genotoxic hazard was identified, in healthy adult patients who undergo low-stress surgery.